A Study of Accounting Information System Adoption in the Small and Medium Companies in Libya: A Technology Acceptance Model Approach - Omran, Mustafa I. O. (2010)
The small and medium sized companies in Libya are fast growing industry in Libya and there is a lot of potential and opportunities in this area from investment perspective. Due to uncertainty and geographic location in the region the SME's in Libya are providing very limited performance and mostly the Libyan economy is depending on Oil production. SME's are largest proportion of economics pillar in a country and it need to contribute through their small business efforts. In many countries, SME's has important role in creating employment and supporting economic growth. On the other hand these companies are lacking behind in term of adopting accounting information system among the SME's. The study is based on perceive ease of use, perceive usefulness and intention to use influencing dependent variable as AIS adoption among the SME's. Secondly the SME's are not satisfied, with the technology or the tool which is use to monitor accounting methods, as SME's adoption of AIS is one of the important factor that can influence companies performance and fulfill the audit requirements. Due to all the above reason these SME's are needed to find the ways to strategies there accounting base activities through AIS, as there is very limited research has been prevailed by Libyan SME's to improve their financial operational through AIS. The Libyan companies need strategic leaders who can create organization culture to influence to implement AIS practices and in the end of the day these SME's can have better performance. This study is unique as there are very few studies on Libyan SME's to measure adoption of AIS and this research have been never conducted on Libyan SME's before. This study will add value by providing a significant contribution towards adoption of AIS practices among the Libya SME's.